2015
DOI: 10.1063/1.4935112
|View full text |Cite
|
Sign up to set email alerts
|

Large-eddy simulation of turbulent flow and dispersion over a matrix of wall-mounted cubes

Abstract: Articles you may be interested in A stochastic perturbation method to generate inflow turbulence in large-eddy simulation models: Application to neutrally stratified atmospheric boundary layers Phys. Fluids 27, 035102 (2015); 10.1063/1.4913572 Constrained large-eddy simulation of wall-bounded compressible turbulent flows

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Additional affinity can also be identified in the tendency of both categories of systems to develop turbulence or relatively chaotic solutions in some circumstances, i.e., large values of the Reynolds and Marangoni numbers, respectively (both account for the strength of horizontally directed flow). In the wind-obstacles problem, such complex states are essentially the outcome of purely hydrodynamic effects and related bifurcations [18,[42][43][44][45][46][47][48][49][50].We have shown that if hybrid buoyancy-Marangoni convection induced by hot blocks in liquid metals is considered, the frequency spectra still align with the Kolmogorov law in a certain range of frequencies.…”
Section: Discussionmentioning
confidence: 86%
“…Additional affinity can also be identified in the tendency of both categories of systems to develop turbulence or relatively chaotic solutions in some circumstances, i.e., large values of the Reynolds and Marangoni numbers, respectively (both account for the strength of horizontally directed flow). In the wind-obstacles problem, such complex states are essentially the outcome of purely hydrodynamic effects and related bifurcations [18,[42][43][44][45][46][47][48][49][50].We have shown that if hybrid buoyancy-Marangoni convection induced by hot blocks in liquid metals is considered, the frequency spectra still align with the Kolmogorov law in a certain range of frequencies.…”
Section: Discussionmentioning
confidence: 86%
“…Today, the choice to restrict to strongly idealized geometries like uniform buildings arrays is not so much motivated by cost considerations, as by advantages for the study of fundamental turbulence aspects and parameterizations that can be substantiated by a relative abundance of corresponding windtunnel measurements (e.g. Boppana et al, 2010;Gu et al, 2011;Inagaki et al 2012;Saeedi and Wang, 2015;Goodfriend et al 2016;Castro et al 2017;Llaguno-Munitxa et al, 2017). However, in order to investigate the full range of complex geometry-induced flow and dispersion patterns of real cities, studies have to be expanded to realistic, vertically and horizontally heterogeneous canopies (see for example comments on Kanda et al, 2013 and references therein).…”
Section: Introductionmentioning
confidence: 99%